1977
DOI: 10.1111/j.1528-1157.1977.tb04463.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacological Aspects of Valproate Sodium

Abstract: Summary A series of clinical‐pharmacological paramétérs implied in the compound valproate sodium (VPA) have been studied, e.g., the correlation between daily doses and attained serum concentrations of the drug during the steady state, the daily fluctuations in concentrations of VPA in serum, the half‐life of VPA after chronic treatment of patients, the degree of protein binding, and the ratio of VPA concentration in CSF to its concentration in serum. In addition, calculation of the half‐life of VPA after admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…1973). Similar findings were obtained by Johannessen (1977) and Wulff et al (1977). When CSF le~els of valproic acid were comp~red with the unbound drug concentration in plasma they were found to be identical.…”
Section: Valproic Acid In Cerebrospinal Fluidsupporting
confidence: 87%
“…1973). Similar findings were obtained by Johannessen (1977) and Wulff et al (1977). When CSF le~els of valproic acid were comp~red with the unbound drug concentration in plasma they were found to be identical.…”
Section: Valproic Acid In Cerebrospinal Fluidsupporting
confidence: 87%
“…The drug was still present 24 hours after a single dose. The half-life of valproic acid was about 10 hours (8-10 hours), which is in good agreement with the times reported in the literature (11)(12)(13)(14).…”
Section: Recoverysupporting
confidence: 87%
“…A concentration–response design is a better method than a dose–response design because the latter does not take into account the interindividual variablity in age, weight, or absorption and rate of elimination of the study drug. Indeed, studies have shown that specific doses of DVPX produce a wide range of plasma VPA concentration in different patients (Loiseau et al, 1975; Wulff et al, 1977; Levy, 1984).…”
Section: Discussionmentioning
confidence: 99%